Pengaruh keaktifan belajar terhadap kemampuan pemecahan masalah matematis siswa SMA pada materi fungsi kuadrat - Juniantika, Muhammad Ikhsan; Sari, Rika Mulyati Mustika; Kartika, Hendra (IKIP Siliwangi, 2024)
The purpose of this study is to ascertain how learning activities affect students' capacity to solve mathematical problems involving quadratic functions. Because of the weight placed on students' capacity to solve mathematical problems, the findings of this study should assist educators in implementing instructional strategies that prioritize learning activities. 81 students served as the sample for this study, which was carried out in one of Karawang City's State Senior High Schools. The quantitative Expost Facto method and strategy were employed in this investigation. Simple random sampling was the method used to acquire the data, and simple linear regression was the method utilized to analyze the data using the normalcy, linearity, and hypothesis tests. With a Sig value of.000, it is evident that learning activities have a significant impact on students' ability to solve mathematical problems. The regression equation is Y = 59.674 + 0.408X, and the influence is 23.3%. The findings also indicate a positive relationship, indicating that students' ability to solve mathematical problems will increase with activity level.